Predictors of intestinal pseudo-obstruction in systemic lupus erythematosus complicated by digestive manifestations: data from a Southern China lupus cohort. (March 2016) - Huang, Q; Lai, W; Yuan, C; Shen, S; Cui, D; Zhao, J; Lin, J; Ren, H; Yang, M
Objective: To determine factors that may predict intestinal pseudo-obstruction (IpsO) in systemic lupus erythematosus (SLE) patients complicated by digestive manifestations. Methods: SLE patients with digestive manifestations ( n = 135) were followed at Southern Medical University affiliated Nanfang Hospital from 2000 until 2013. Demographic variables, clinical features, and laboratory data were compared between the two groups. Univariate and multivariate logistic regression models were used to establish factors that predispose to IpsO in these patients. Results: At the end of the study period, 32 (23.7%) patients had developed IpsO. Mortality (9 patients) was infrequent and the cause of death was unrelated to IpsO. Independent predictors of IpsO in SLE were ureterectasia, anti-U1 RNP +, peritonitis, and low C3 levels. Conclusions: Regular abdominal X-ray examinations are recommended in SLE patients with ureterectasia, anti-U1 RNP +, peritonitis, or low C3 levels, as early diagnosis and therapy may prevent unnecessary surgical intervention and improve the disease course.